O poder judiciário no presidencialismo de coalizão: introdução para uma análise institucional do poder judiciário no Brasil - Mateus Morais Araujo (2012)
The Judiciary hasan increasingly perceptible political role in contemporary democracies. Through the interpretation of laws, but mainly through constitutional jurisdiction, the judiciary applies, modifies, rebuilds or invalidates laws enacted by governments. The phenomenon of global expansion of the judicial power is known as judicialization of politics. In light of the connection between judicial, legislative and executive branches in Brazil, this thesis explores how they are related in the context of coalition presidentialism. The analysis suggests the existence of a political role of the judiciary branch controlled by its institutional design, especially the procedure of composition of the Brazilian Supreme Court - STF, the highest court with ultimate appellate jurisdiction. This structure which adds coalition presidentialism and the political process ofappointment Justices to STF results in a court with little activity, with procedural convergence with government preferences and a judiciary with lower, but not insignificant, political impact.